Multiregion sequencing reveals the intratumor heterogeneity of driver mutations in TP53‐driven non‐small cell lung cancer. Issue 1 (3rd October 2016) - Zhang, Le‐Le; Kan, Mengyuan; Zhang, Man‐Man; Yu, Sha‐Sha; Xie, Hui‐Jun; Gu, Zhao‐Hui; Wang, Hai‐Ning; Zhao, Shuang‐Xia; Zhou, Guang‐Biao; Song, Huai‐Dong; Zheng, Cui‐Xia
Abstract : Intratumor heterogeneity (ITH) in non‐small cell lung cancer (NSCLC) may account for resistance after a period of targeted therapies because drugs destroy only a portion of tumor cells. The recognition of ITH helps identify high‐risk patients to make effective treatment decisions. However, ITH studies are confounded by interpatient heterogeneity in NSCLC and a large amount of passenger mutations. To address these issues, we recruited NSCLC patients carrying TP53 mutations and selected driver mutations within recurrently mutated genes in NSCLC. A total of 12‐paired normal‐tumor tissues were subjected to whole‐genome/whole‐exome sequencing. From these, 367 non‐silent mutations were selected as driver mutations and deeply sequenced in 61 intratumoral microdissections. We identified a universal prevalence of heterogeneity in all 12 tumors, indicating branched evolution. Although TP53 mutations were observed in single biopsy of all 12 tumors, most tumors consist of both TP53 mutated and non‐mutated cells in separate regions within the same tumor. This suggests the late molecular timing of the acquisition of TP53 mutations; therefore, the detection of TP53 mutations in a single biopsy may simply not reflect the early malignant potential. In addition, we identified regions of loss of heterozygosity surrounding TP53 and CDKN2A mutations in tumor 711, which also exhibited heterogeneity in different regional samples. Because the ITH of driver mutations likely has clinical consequences, further efforts are needed to limit the impact of ITH and to improve therapeutic efficiency, which will benefit NSCLC patients receiving targeted treatments. Abstract : What's new? Intratumor heterogeneity (ITH) in non‐small cell lung cancer (NSCLC) may account for resistance during targeted treatment. Identifying ITH could help make effective treatment decisions, but ITH studies have so far been hampered by confounding factors. To reduce the interference of interpatient heterogeneity and passenger mutations, the authors recruited NSCLC patients with TP53 mutations and selected potential driver mutations. They identified extensive ITH of driver mutations in all NSCLC tumors and demonstrated the late molecular acquisition of TP53 mutation during tumor progression in most patients. The data highlight the clinical potential of limiting the impact of ITH for NSCLC targeted treatment.